Arrayed free space continuous-wave terahertz photomixers - Bauerschmidt, Sebastian; Döhler, Gottfried; Lu, Hong; Gossard, Art; Malzer, Stefan; Preu, Sascha (Optics Letters, 2013)
We present free space coherent arrays of continuous-wave terahertz (THz) photomixers and compare the results to on-chip arrays. By altering the relative phases of the exciting laser signals, the relative THz phase between the array elements can be tuned, allowing for beam steering. In addition, the constructive interference of the emission of N elements leads to an increase of the focal intensity by a factor of N2 while reducing the beam width by ∼N-1, below the diffraction limit of a single source. Such array architectures strongly improve the THz power distribution for stand-off spectroscopy and imaging systems while providing a huge bandwidth at the same time. We demonstrate this by beam profiles generated by a 2 × 2 and a 4 × 1 array for a transmission distance of 4.2 m. Spectra between 70 GHz and 1.1 THz have been recorded with these arrays. © 2013 Optical Society of America.
Keywords: Terahertz emitter array; beam steering